Kosovo Liberation Army : the inside story of an insurgency - Perritt, Henry H., Jr., 1944- (University of Illinois Press, 2008)
Provides a historical background of the Kosovo Liberation Army (KLA) and its activities up to the NATO intervention at the end of the 20th century.